2022
DOI: 10.53430/ijsru.2022.4.2.0072
|View full text |Cite
|
Sign up to set email alerts
|

Dual positivity of HIV and anti-HCV in the highly infected population of Rivers State, Nigeria

Abstract: The study looked to establish dual positivity of human immunodeficiency virus (HIV) and anti-hepatitis C virus (HCV) antibody among HIV-infected individuals in Port Harcourt, Nigeria. Plasma samples from 89 HIV-infected individuals presenting at the Retroviral Clinic of the University of Port Harcourt Teaching Hospital (UPTH), Rivers State, Nigeria, were assayed for anti-HCV-antibody. Seropositivity of anti-HCV-antibody was detected with ELISA kits. Variables tested include sex, age group, educational status, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 0 publications
6
5
2
Order By: Relevance
“…The incidence among university students was zero (0.0%). This observation runs counter to a recent study by Okonko et al (2022) that found a higher frequency among patients with tertiary education and a study by Onyekwere et al (2016) that found a higher prevalence among people with no formal education. The numbers here also differ from what they found in their survey, where the prevalence of those without formal education was 4.0%, and those with elementary education was 1.8%.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The incidence among university students was zero (0.0%). This observation runs counter to a recent study by Okonko et al (2022) that found a higher frequency among patients with tertiary education and a study by Onyekwere et al (2016) that found a higher prevalence among people with no formal education. The numbers here also differ from what they found in their survey, where the prevalence of those without formal education was 4.0%, and those with elementary education was 1.8%.…”
Section: Discussioncontrasting
confidence: 99%
“…The prevalence of HCV Ab and marital status were not related (p > 0.05). This outcome supports our earlier investigation in Port Harcourt, Nigeria (Okonko et al, 2022). When compared to the study of , where they discovered a higher incidence among single respondents (4.1%) than married ones (2.2%), this observation was marginally higher.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Its endemicity has long been validated in Nigeria, but there is less information about its epidemiology (Riou et al, 2016; Abeni et al, 2020; Okonko & Ernest Nwagwu, 2023). There is an established relationship between HIV positivity and the progression of HCV infection; dual positivity with HIV influences the clinical outcome of HCV infection (Villano et al, 1999; Thomas et al, 2000; Sulkowski & Thomas, 2003; Ogbodo et al, 2015; Okonko et al, 2022). The alarming statistics have made it crucial that studies be also done to ascertain the HIV/HCV coinfection prevalence in the country and host factors which may influence the coinfection (Cookey et al, 2021).…”
Section: Introductionmentioning
confidence: 99%